The Black Pearl - ODell, Scott (Boston Houghton Mifflin Company, 1967)
Ramon Salazar grew up knowing many things. Some were true facts that one day he would become a partner with his father, pearling the waters of Baja California. Some, perhaps, were not facts, like the stories his mother told him about the Manta Diablo. This monster of the sea had the shape of kite, but was as large as the largest ship in the harbor of La Paz, withseven rows of teeth in his mouth, Ramons mother said. Other mothers and fathers and grandfathers in the village described the Manta Diablo defferently, but all agreed that the Manta was there in the Vermilion Sea and he was the most dangerous creature in it.
Keywords: Children Literature